PENDAYAGUNAAN REPOSITORI KEMENTERIAN PERTANIAN DALAM MENDUKUNG AKSES TERBUKA INFORMASI IPTEK PERTANIAN INDONESIA - Nana Sutarsyah; Akhmad Syaikhu HS; Herwan Junaidi (Perpustakaan Nasional RI, 2021)
Introduction. Management of agricultural science and technology information in the form of an Institutional Repository is one of the efforts of PUSTAKA as the deposit center of the Ministry of Agriculture's publications. Purpose. The purpose of the study is to determine the utilization of the Ministry of Agriculture repository in supporting open access to information on Indonesian Agricultural Science and Technology. Purpose. The assessment was carried out through direct observation on the Ministry of Agriculture's web repository, from April 1–14, 2020. Results and Discussion. The results of the study suggested that the average number of users of the repository was 3,000 users / day.The highest number of users was April 14, 2020, which was 3,800 users / day, while the lowest number of users was April 10, 2020, which was 2,800 users / day. The total number of users presented on the user graph for 2 weeks was 44,698. The country of origin for most users accessing the repository of the Ministry of Agriculture is Indonesia. As much as 2.75% users performedthe web searchusing ‘BPTP Jateng’ (Central Java) as keywords.